Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1089/lgbt.2019.0306
|View full text |Cite
|
Sign up to set email alerts
|

Medicare Prescription Drug Plan Coverage of Hormone Therapies Used by Transgender Individuals

Abstract: Purpose: Although pharmacologic hormone therapy represents one of the mainstays of gender-affirming therapy for transgender individuals, there are many access barriers for these therapies, including insurance coverage of these drugs. The purpose of this study was to examine Medicare coverage of hormone therapies used by transgender individuals. Methods: Using Centers for Medicare and Medicaid Services prescription drug plan formulary files, we determined plan coverage, coverage restrictions, and out-of-pocket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…7 Even for people with insurance, reports of insurance denials are common, 8 and many people report that deductibles and other out-of-pocket costs like copays and coinsurance for hormones and surgeries are a major economic barrier to pursuing gender-affirmation care. 9 One study using Centers for Medicare and Medicaid Services prescription drug plan formulary files found that out-of-pocket costs for gender-affirming hormone therapy can be substantial, ranging between $84 to $2,716 in 2010 and from $72 to $3,792 in 2018. 10 Moreover, insurers often require proof of referral letters for hormone initiation as well as surgical procedures from mental health professionals, which can also serve as a limiting factor given the inadequate workforce capacity of gender-affirming therapists, counselors, social workers, primary care providers, and surgeons, particularly in geographical areas that are prone to insurance network inadequacy issues and policy restrictions in the US.…”
Section: Introductionmentioning
confidence: 99%
“…7 Even for people with insurance, reports of insurance denials are common, 8 and many people report that deductibles and other out-of-pocket costs like copays and coinsurance for hormones and surgeries are a major economic barrier to pursuing gender-affirmation care. 9 One study using Centers for Medicare and Medicaid Services prescription drug plan formulary files found that out-of-pocket costs for gender-affirming hormone therapy can be substantial, ranging between $84 to $2,716 in 2010 and from $72 to $3,792 in 2018. 10 Moreover, insurers often require proof of referral letters for hormone initiation as well as surgical procedures from mental health professionals, which can also serve as a limiting factor given the inadequate workforce capacity of gender-affirming therapists, counselors, social workers, primary care providers, and surgeons, particularly in geographical areas that are prone to insurance network inadequacy issues and policy restrictions in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrate that self-pay or “other” payment methods had lower hospital costs per stay compared to private insurance. In contrast, Medicare had a significantly higher association with hospital cost per stay, possibly due to improved coverage for gender-affirming surgery and hormone therapy since 2014 ( 39 ). However, despite improved coverage, hormone therapies remain expensive, and prior authorizations and formulary restrictions mitigate advances ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to lack of access to hormone therapy, which is an important component of health and gender-affirming care [ 91 , 92 ]. Even with insurance, coverage of masculinizing hormone therapy can vary from 5% to 75%, and coverage of feminizing therapies can vary from 13% to 100% [ 93 ]. Lack of access and coverage can lead to sourcing hormone-related medications from unreliable sources, such as the internet [ 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%